THE MENTAL HEALTH CARE MODEL TO SUPPORT THE COMMUNITY DURING THE COVID-19 PANDEMIC IN THAILAND - Onpicha Ketphan; Siripattra Juthamanee; Sarah Jane Racal; Dussanee Bunpitaksakun (Belitung Nursing Journal, 2020)
The COVID-19 pandemic has caused people worldwide, such as in Thailand, to be frightened of being infected from the coronavirus. Exposure to media - including unreliable news sources - trigger people's stress and anxiety. This leads to increased mental health problems and psychiatric disorders in the population, resulting in higher suicide rates. Furthermore, this also affects medical and public health care staff working until emotional exhaustion and physical health deterioration. The ongoing fight against the outbreak of the COVID-19 virus increases the likelihood of pressure, stress, and anxiety. Therefore, a mental health care model for the people of Thailand is necessary. With the appropriate format for people to receive correct information, people will be more likely to accept changes, think logically and positively, not be discouraged, and be ready to improve themselves and their mental health.